DBS-platform for biomonitoring and toxicokinetics of toxicants: proof of concept using LC-MS/MS analysis of fipronil and its metabolites in blood - Raju, Kanumuri Siva Rama (Sci Rep, 2016)
A simple, sensitive and high throughput LC-MS/MS method was developed and validated for quantification of fipronil, fipronil sulfone and fipronil desulfinyl in rat and human dried blood spots (DBS). DBS samples were prepared by spiking 10 μl blood on DMPK-C cards followed by drying at room temperature. The whole blood spots were then punched from the card and extracted using acetonitrile. The total chromatographic run time of the method was only 2 min. The lower limit of quantification of the method was 0.1 ng/ml for all the analytes. The method was successfully applied to determine fipronil desulfinyl in DBS samples obtained from its toxicokinetic study in rats following intravenous dose (1 mg/kg). In conclusion, the proposed DBS methodology has significant potential in toxicokinetics and biomonitoring studies of environmental toxicants. This microvolume DBS technique will be an ideal tool for biomonitoring studies, particularly in paediatric population. Small volume requirements, minimally invasive blood sampling method, easier storage and shipping procedure make DBS a suitable technique for such studies. Further, DBS technique contributes towards the principles of 3Rs resulting in significant reduction in the number of rodents used and refinement in sample collection for toxicokinetic studies.